Biodegradable Carriers for Delivery of VEGF Plasmid DNA for the Treatment of Critical Limb Ischemia - Liu, Guang; Fang, Zhiwei; Yuan, Minglu; Li, Weimin; Yang, Yunqi; Jiang, Mier; Ouyang, Yuanming; Yuan, Weien (Frontiers in Pharmacology, 2017)
The safe and efficient delivery of therapeutic nucleic acid is a prerequisite for an effective DNA therapy. In this study we condensed the low molecular weight polyethylenimine (PEI, 1.8k Da) with 2,6-pyridinedicarboxaldehyde (PDA), both of which are degradable in vivo, to synthesize a biodegradable polycationic material (PDAPEI) to deliver vascular endothelial growth factor (VEGF) plasmid DNA (pDNA). Particle size and zeta potential of this novel degradable PEI derivatives-pDNA nanoparticle were investigated and in vitro cytotoxicity was estimated on human umbilical vein endothelial cells (HUVECs). Using pDNA encoding VEGF-A and green fluorescence protein (GFP), we also checked transfection efficiency of the vector (PDAPEI) and found its excellent performance at 40 w/w ratio. We successfully established peripheral ischemia animal model on C57/BL6J mice to evaluate the therapeutic effect of PDAPEI/pVEGF-A polyplex system on ischemic disease and a conclusion was made that PDAPEI is a promising gene vector in the treatment of peripheral ischemic artery disease.